“Parenting with Rumah Keluarga Risman” Facebook group as information society and determinant of technology function - Tri Juniati Andayani; Zainal Abidin Achmad (Indonesian Journal of Social Sciences, 2020)
The information society uses the means of information technology with high intensity in everyday life. Facebook groups provide function as an information society. One of the unique groups is “Parenting with Rumah Keluarga Risman” as the research subject. This qualitative research uses the virtual ethnography method to observe both real field and virtual field. As observer-participants, researchers conducted virtual inquiries and in-depth interviews with informants of the research subject. The members of the “Parenting with Rumah Keluarga Risman” Facebook group represent their selves whether as a real community and a virtual community. This community often holds meetings in a public space of a city. The intensity of this virtual community is more intensive when having shared problems. The group provides many useful information about parenting, such as avoiding pornographic content for children, book discussions, and social agenda. The communication intimacy among members exceeds the real community. The contents of the communication discussing knowledge parenting in Islamic perspective. The results showed this Facebook group is a concrete form of the concept of determination of technology and information society.